MENINGKATKAN TRANSPARANSI DAN DISIPLIN PASAR PERBANKAN SYARIAH DI INDONESIA - Hasan Hasan (Economica: Jurnal Ekonomi Islam, 2013)
Supervision and market discipline is an act of market participants in response to the performance and risk of the bank. Market discipline has realized its importance in supporting the creation of a sound banking, and has been adopted in the Basel II as one of the pillars of sound banking. One of the prerequisites of effective market discipline is the transparency of bank information to market participants. Transparency and market discipline in Islamic banks are becoming more important as application -sharing system, in which the Islamic bank depositors are theoretically exposed to a higher risk than conventional bank customers who receive definitive results. The importance of transparency and market discipline in Islamic banks has been realized with the formulation of the principles of transparency and disclosure of information in order to improve market discipline on banks by the sharia Islamic Financial Services Board (IFSB) in 2007.This paper examines the theoretical framework of market discipline, the principles of transparency in promoting Islamic banking market discipline prepared by the IFSB, and various disciplines of research results in the banking market and the Indonesian Islamic banking. From the results of this study, formulated a variety of challenges and things that need to be considered to improve transparency and encourage market discipline of Islamic banking in Indonesia. At the end, delivered various subsequent recommendations to improve transparency and market discipline practices of Islamic banking in Indonesia.